Experimental Analysis of Thermo‐mechanical Behaviour of Electronic Components with Speckle Interferometry. (17th October 2013) - Casavola, C.; Lamberti, L.; Moramarco, V.; Pappalettera, G.; Pappalettere, C.
ABSTRACT Experimental investigations of thermo‐mechanical behaviour of electronic components may help to prevent catastrophic in‐service failures. Non‐contact optical techniques such as speckle and moiré interferometry are naturally suited for carrying out measurements on electronic equipment as they are non‐invasive techniques and provide high‐resolution full‐field information on displacements. In spite of its inherent ability to measure deformations at the nanometer level, there are few examples of application of speckle interferometry to true monitoring of thermo‐mechanical behaviour of electronic components in real time. For this reason, the paper presents a phase shifting electronic speckle pattern interferometry (PSESPI) experimental set‐up developed in order to monitor the time evolution of thermal deformations in electronic components for aerospace applications submitted to normal or anomalous working conditions. Cyclic loads are also analysed to assess fatigue behaviour. Experimental results obtained for whole electronic boards and single components mounted on board fully demonstrate the capability of PSESPI to detect even small differences in thermo‐mechanical response between normal and anomalous functioning.